Ibnu Sina’s Educational Methodology in Character Building and its Relevance to the Merdeka Curriculum: (Metodologi Pendidikan Ibnu Sina dalam Pembentukan Karakter dan Relevansinya terhadap Kurikulum Merdeka) - Arina Nur Sofiana; Dewi Rizqa Tamia; Nur Saidah (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This systematic literature review (SLR) synthesizes Ibnu Sina’s educational methodology in shaping student character, focusing on peer-reviewed publications from 2020 to 2025. Modern Islamic education is challenged by ethical crises and digital addictions, making classical integrations of science and spirituality highly relevant. Utilizing the PRISMA 2020 framework, 30 articles were selected from reputable databases and appraised using Joanna Briggs Institute (JBI) tools. The findings establish that character building is rooted in the ontology of the soul, operationalized through an age-based gradual curriculum (tadrij), rigorous educator requirements, and seven instructional methods. This review bridges classical psychology and modern educational frameworks by linking Ibnu Sina’s rational soul with metacognition, demonstrating its alignment with the Indonesian Kurikulum Merdeka, and proposing the Blended Spiritual-Connected Learning (BSCL) model to govern digital interactions in Society 5.0. Ultimately, cohesive school-family alliances and enhanced digital-spiritual professional standards for teachers are recommended to foster the insan kamil.